TRANSMISSION OF MYCOPLASMA BOVIGENTALIUM FROM EXPERIMENTALLY INFECTED BULLS TO COWS BY NATURAL ‎SERVICE.‎ - Mehdi, H.; A.R. Fathalla, M.; M. Al-Aubaidi, J. (The Iraqi Journal of Veterinary Medicine, 1986)
Four Friesian bulls 3-6 Years old four Friesian heifers 18-24months old were used in this study. Three bulls were injected with 3 ml 3 davs old Mycoplasma bovigenitalium strain AL culture. One bull served as a control which recived broth only. Mycoplasma bovigenitalium organisms serologically similar to the injected strain was isolated from the experimental bulls. All the bullsshowed clinical signs of seminal vesiculitis with varying degress. Two of the infected bulls were left to service 4 clean virgin heifers for four months. All heigers required more than three services to concieve. Mycoplasma bovigenitalium serologically similar to the experimental strain was isolated from three cows at different periods.